Glass Formation and Ionic Conduction Behavior in GeSe2–Ga2Se3–NaI Chalcogenide System. Issue 12 (25th August 2015) - Zhai, Sumin; Li, Legang; Chen, Feifei; Jiao, Qing; Rüssel, Christian; Lin, Changgui
Abstract : Series of glassy and glass‐ceramic samples in the GeSe2 –Ga2 Se3 –NaI system is prepared by melt‐quenching technique and the glass‐forming region is well‐defined by XRD investigations. Na‐ion conduction behavior is systemically studied by impedance measurements. For the glasses in the series (100−2 x )GeSe2 – x Ga2 Se3 – x NaI, ionic conductivities increased with increasing x, whereas the attributed activation energy of ion conduction decreases. The enhanced mechanism is discussed by employing Raman spectra. In addition, the effect of the crystal phases NaI and Ga2 Se3 on the ionic conduction behavior in the (70− x )GeSe2 – x Ga2 Se3 –30NaI samples is discussed. Although it shows that the poorly conducting crystallites of NaI and Ga2 Se3 have a negative effect on the ionic conductivities in this series, the highest ionic conductivity of 1.65 × 10 −6 S/cm is obtained in the 45GeSe2 –25Ga2 Se3 –30NaI glass. Finally, this study also demonstrates a possible way to search appropriate Na‐ion solid electrolytes for all‐solid‐state batteries.